Consumer regulation against abusive clauses - Rodríguez Chávez, Reyler Yulfo (2012)
In this paper, we address the existing consumer protection mechanisms against abusive clauses in consumer contracts adopted in line with or pursuant to general contracting laws. Although these contractual modalities currently reigning in the market have the advantage of establishing quick and efficient legal relationships between suppliers and consumers, thereby reducing costs of transactions to a minimum (time, money and effort invested in entering into contracts in the market), they are contracts in which suppliers develop all of their financial power and their prevalence in the management of information, including abusive clauses in contracts that disturb the balance between the rights and obligations of consumers, thereby restricting, reducing or excluding their rights or increasing their contractual obligations and costs, in violation of the principle of good faith and contractual fairness. To counteract abusive clauses, a set of consumer protection measures have been implemented, ranging from the protection of private interests of directly wronged consumers to consumer representative associations, and even to the so-called self restraint of suppliers. The State has also implemented protection measures, grouped in controls of an administrative, legislative and judicial nature, aimed at protecting consumers by preventing or, if necessary, counteracting the harmful effects of abusive contractual terms in consumer contracts.